Ethnoscience Approach to Improve Science Literacy on Chemical Bonding: A Thematic Synthesis - Suwandi, Sukma Yanti Putri Ayu; Sukarmin, Sukarmin; Cahyaningrum, Sari Edi; Satriawan, Muhammad; Soraya, Fathimah (FKIP Universitas Lampung, 2025)
This study aims to comprehensively examine the implementation of the ethnoscience approach in teaching chemical bonding and its contribution to improving students' science literacy, particularly at the high school level. The ethnoscience approach is believed to be able to connect abstract scientific concepts with local cultural values, practices, and artifacts, thereby making learning more contextual, meaningful, and relevant to students' lives. The research method employed is a systematic literature review, utilizing the PRISMA framework. The initial search process identified 100 articles from various reputable databases. These articles were selected based on predefined inclusion and exclusion criteria, resulting in 20 articles that met the criteria for in-depth analysis. The analyzed articles were published between 2022 and 2025 and indexed in SINTA and Scopus databases. The synthesis results showed that most studies reported an increase in science literacy through the integration of local culture in chemistry learning. The most dominant learning models were project-based learning and inquiry, followed by contextual learning, as well as other approaches that emphasized active student involvement. Ethnoscience integration was applied at various levels, with a primary focus on junior high and senior high schools, and to some extent on teachers or general contexts. The forms of local wisdom used varied, including regional traditions, batik, and wayang, which were generally combined with innovative learning media to connect chemical concepts with socio-cultural realities. The main findings confirm that the ethnoscience approach not only contributes to improving students' conceptual understanding, critical thinking skills, and scientific attitudes but also fosters awareness and appreciation of local culture. This pattern also reflects the trend of culture-based learning innovation in Indonesia, which is increasingly relevant in addressing the demands of the Merdeka Curriculum. Thus, the application of ethnoscience is recommended as an effective strategy to enhance science literacy while preserving the nation's cultural values. Keywords: systematic literature review, science literacy, chemical bonds.